2000
DOI: 10.1063/1.126636
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical passivation of gallium arsenide surface with organic self-assembled monolayers in aqueous electrolytes

Abstract: Self-assembled monolayers of octadecylthiol (ODT) were reconstituted on freshly etched gallium arsenide (n-GaAs) for the electrochemical stabilization against decomposition of the surfaces (passivation) in aqueous buffers. The surface composition was evaluated by x-ray photoelectron spectroscopy to optimize the surface treatment before ODT deposition. Electrochemical properties of the monolayers were monitored by cyclic voltammetry and impedance spectroscopy. The impedance spectrum of the photoetched n-GaAs af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 14 publications
1
63
1
Order By: Relevance
“…However, effects of the surface modification on the luminescence properties have been discussed in terms of increased PL intensity and PL decay time only for bulk GaAs [15,16]. In previous studies, we demonstrated the electrochemical stabilization of the GaAs surface by the ODT monolayer deposition in aqueous electrolytes [2]. The ODT monolayers turned out to be stable even after more than one month in air [8].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, effects of the surface modification on the luminescence properties have been discussed in terms of increased PL intensity and PL decay time only for bulk GaAs [15,16]. In previous studies, we demonstrated the electrochemical stabilization of the GaAs surface by the ODT monolayer deposition in aqueous electrolytes [2]. The ODT monolayers turned out to be stable even after more than one month in air [8].…”
mentioning
confidence: 95%
“…This may be used to investigate changes in the density of surface states. Recently, the electrochemical passivation of GaAs surfaces in aqueous electrolytes with self-assembled monolayers (SAMs) of octadecylthiol (ODT) has been reported [2]. Here we discuss effects of ODT monolayer deposition on the QD PL in air.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[21] It was recently suggested that ODT surfaces, assembled with a photochemical etching method, keep impedance spectra stable for several hours in an aqueous electrolyte solution under conditions of zero-current potential. [22] Further, as a promising alternative to the surface passivation of gallium arsenide with organic monolayers, benzoic and dicarboxylic acid derivatives have been introduced. [23±25] Their chemisorption to GaAs has been shown to control the work function of the semiconductor, [23] and the compatibility of the resulting interface with at least some biological environments has recently led to the development of the first GaAs-based biosensor for the direct detection of micromolar levels of nitric oxide under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated the electrochemical passivation of GaAs surfaces with monolayers of alkylthiols under physiological conditions, i.e., at neutral pH in aqueous electrolytes [3,4]. Suppression of the surface state density due to the covalent As-S coupling could also be observed by photoluminescence signals from near-surface InAs quantum dots [5].…”
Section: Introductionmentioning
confidence: 97%